Literature review and appraisal on alternative neurotoxicity testing methods. Issue 4 (27th April 2018) - Masjosthusmann, Stefan; Barenys, Marta; El‐Gamal, Mohamed; Geerts, Lieve; Gerosa, Laura; Gorreja, Adriana; Kühne, Britta; Marchetti, Natalia; Tigges, Julia; Viviani, Barbara; Witters, Hilda; Fritsche, Ellen
Abstract : The goal of this review was the evaluation of information on assessment methods in the field of alternative neurotoxicity (NT) testing. We therefore performed a systematic and comprehensive collection of scientific literature (in English) from the past 27 years until mid of 2017 on state of the art alternative testing methods including in vitro test methods, in silico methods and alternative non‐mammalian models. This review identified a variety of test methods that have the ability to predict NT of chemicals based on predefined key NT endpoint categories (27). Those endpoint categories were derived from the Mode of Action (MoA) of known human neurotoxicants. Pre‐evaluated MoAs of human neurotoxicants allowed the identification of performance characteristics with regard to the ability of a test system to correctly predict a chemical effect on an endpoint category. The most predictive in vitro model that covers a large variety of endpoint categories are primary rodent cells or tissues. Human based systems derived from induced pluripotent stem cells (iPSC) are promising and warrant human relevance. There is however not yet sufficient data on these models to demonstrate their suitability to reliably substitute primary rodent cells for NT testing purposes. Test methods for glia toxicity are rare and glia endpoint categories are clearly underrepresented. Therefore, a focus for future method development should be placed on glia, astrocytes, oligodendrocytes and microglia based models, preferably in a co‐culture se up. The review on in silico methods, resulted into 54 QSARs publications, relevant for NT, of which 39 on blood brain barrier (BBB) permeation. The QSARs available in the publications were developed from data on drugs and chemicals, but there appears a limited set of experimental data for chemicals and pesticides on blood‐brain barrier passage. The evaluation of NT methods using alternative whole organism approaches demonstrated a majority of data for C. elegans (nematode species), represented with high true prediction (96%). The main endpoint category was inhibition of cholinergic transmission, with specific endpoints for AChE activity and motor activity, the latter confirming the added value of a whole organism approach among alternative models. Though D. rerio, the zebrafish model appeared a promising model for DNT studies with numerous advantages, it was poorly evaluated for NT endpoints. Next to the need for standardized protocols using C. elegans as a test organism, the zebrafish model needs further exploration for NT relevant endpoints. In conclusion, a NT alternative test battery covering identified and relevant MoA for NT is recommended. Therefore, test methods with relevant controls and standard operation procedures have to be set up for covering most important MoA. To link the human in vitro testing to rodent in vivo studies and validate the stem cell‐derived systems, it is advised to include rodent primary cultures into the studies. For more complex, behavioural readout, effects in alternative organisms should be combined with electrophysiological assessments in vitro.